Pengaruh Gaya Hidup dan Citra Merek Terhadap Minat Beli Konsumen - Ira, Isma Wati; Haedar, Haedar; Sulfitrah, Sulfitrah (Income : Digital Business Journal, 2024)
This study aims to determine whether the influence of lifestyle and brand image has a significant effect simultaneously and partially on the intention to buy an iPhone cellphone in Palopo City. The technique used in this research is purposive sampling. And this method uses a quantitative method using primary data, the data collection method uses a questionnaire survey of 100 respondents using iPhone cellphones in Palopo City. The analysis in this study used multiple linear regression analysis. After the data was collected, the data were analyzed using the SPSS version 23 program. The results of this study were using multiple linear regression analysis using the partial test (T), simultaneous test (F), and testing the coefficient of determination (R2).Based on the results of the study, it shows that simultaneously and partially lifestyle and brand image have a jointly and significantly positive effect on the intention to buy iPhone mobile phones in the city of Palopo. In the model formed by the influence of lifestyle and brand image on buying interest, it is able to explain that the variable of buying interest is 81.4% and the remaining 18.6% is influenced by other variables.